Informations concernant la S.I.E.P.M. (Bulletin de Philosophie Médiévale, 2024)
Abstract 1. S.I.E.P.M. Jacqueline Hamesse Award 2024 2. Minutes of the 109th meeting of the Bureau of the S.I.E.P.M. 3. Minutes of the 110th meeting of the Bureau of the S.I.E.P.M.